PENGARUH MODEL PEMBELAJARAN SEARCH, SOLVE, CREATE, AND SHARE (SSCS) TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK - Nurfayza Chairani; Suprananto Suprananto (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2024)
This study aims to determine whether there is an effect of the Search, Solve, Create, and Share (SSCS) learning model on students' mathematical problemsolving ability and to see how much influence the SSCS learning model has on students' mathematical problemsolving skills.  This research uses a quantitative approach with a quasi-experiment method with a pretest-posttest control group design. The population of this study were all VIII grade students in one of the junior high schools in Bogor Regency. The samples used were class VIII-2 as the control class using conventional learning model and class VIII-4 as the experimental class using SSCS learning model. Data was collected through a mathematical problemsolving ability test in the form of five description questions on Social Arithmetic material. The data obtained were analyzed using T test and Effect Size test. The results of data analysis showed that there was an effect of SSCS learning model on students' mathematical problemsolving ability. The effect size of SSCS learning model on students' mathematical problemsolving ability is 0.39 with moderate category.